Case Report: Suspected intestinal perforation caused by accidental ingestion of magnet - Ke, Mengyu; Yang, Jun (Frontiers in Surgery, 2025)
IntroductionChildren frequently swallow foreign objects, and ingesting magnets on occasion can cause major problems because they are composed of unique materials that draw to one another in the intestinal wall. As a result, there is a significant chance of intestinal wall necrosis, intestinal perforation, and fistula formation. On the basis of the history of magnet ingestion, clinical signs like nausea and vomiting, and x-ray imaging, it is easy to diagnose magnet-induced complications. However, there was no foreign body shadow in the x-ray, and some intermittent swallowing of magnets in different intestinal tubes attracted one another, causing intestinal perforation and subsequent discharge along with the feces.Case presentationWe describe the case of an 8-year-old girl who had been consuming two magnets for six days when she arrived at our hospital's emergency room with sporadic stomach ache and vomiting for two days. The youngster had a history of vomiting yellow-green bile, and a physical examination revealed a noticeable intestinal pattern with noticeable periumbilical discomfort. An abdominopelvic CT scan indicated intestinal obstruction, while an abdominal x-ray indicated minimal distension of the intestinal tube and a fluid level. No obvious foreign body shadow was seen in the abdominal cavity. Laparoscopic exploration revealed two perforations, one in the colon and one in the small bowel; no magnets were found intraoperatively. Intraoperative abdominal radiographs suggested loss of signs of limited intestinal distension and no foreign body was seen. Considering the absence of foreign bodies observed during the operation and the patency of the intestine postoperatively, it is reasonably inferred that the magnet was excreted via feces after causing intestinal perforation. The patient's condition was stable after the operation and she was discharged from the hospital after 9 days.ConclusionThis case emphasizes the necessity of maintaining clinical vigilance in pediatric patients with suspected magnet ingestion, even when imaging fails to identify foreign bodies. Notably, the absence of intraoperatively retrieved magnets does not preclude magnet-induced injuries, and early surgical exploration may contribute to improved clinical outcomes.